2011
DOI: 10.1590/s0100-40422011000800021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolismo, oxidação e implicações biológicas do ácido docosahexaenoico em doenças neurodegenerativas

Abstract: Recebido em 16/8/10; aceito em 20/4/11; publicado na web em 8/7/11 METABOLISM, OXIDATION AND BIOLOGICAL IMPLICATIONS OF DOCOSAHEXAENOIC ACID IN NEURODEGENERATIVE DISEASES. Docosahexaenoic acid (C22:6, n-3, DHA) is a polyunsaturated fatty acid (PUFA) present in large concentrations in the brain and, due to the presence of six double bonds in its structure, is highly susceptible to oxidation by enzymes and reactive oxygen/nitrogen species. The peroxidation of PUFAs has been implicated in an increasing number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 86 publications
(142 reference statements)
0
6
0
5
Order By: Relevance
“…Tzang et al (2009) reported that the consumption of vegetable oils containing PUFAs reduces triglyceride levels, probably because of increased lipase activity. Oxidation of fats and proteins from lipoproteins and cell membranes decreases fat transport causing cell damage and leading to heart disorders (APPOLINÁRIO et al, 2011). LDL transports cholesterol from the liver to peripheral arterial smooth muscle cells, and high LDL levels can cause cholesterol deposition within the arteries of the heart, a risk factor for the development of heart disease (MOREIRA et al, 2010;LUZIA;JORGE, 2011).…”
Section: Weight Evolutionmentioning
confidence: 99%
“…Tzang et al (2009) reported that the consumption of vegetable oils containing PUFAs reduces triglyceride levels, probably because of increased lipase activity. Oxidation of fats and proteins from lipoproteins and cell membranes decreases fat transport causing cell damage and leading to heart disorders (APPOLINÁRIO et al, 2011). LDL transports cholesterol from the liver to peripheral arterial smooth muscle cells, and high LDL levels can cause cholesterol deposition within the arteries of the heart, a risk factor for the development of heart disease (MOREIRA et al, 2010;LUZIA;JORGE, 2011).…”
Section: Weight Evolutionmentioning
confidence: 99%
“…DHA is particularly enriched in synaptosomal membranes and synaptic vesicles, and this enrichment suggests a role for this fatty acid in the central nervous system [1]. DHA is critical for normal brain function, and changes in the quantity and/or oxidation of DHA are associated with neurodegenerative diseases [2-5]. …”
Section: Introductionmentioning
confidence: 99%
“…As for DHA, studies reveal its ability to reduce oxidative stress after injury, in addition to modulating the post‐traumatic inflammatory response . On the other hand, as DHA is a polyunsaturated fatty acid and has several carbon double bonds, it becomes a highly susceptible oxidation target, which can be enzymatic by COX and LOX, or non‐enzymatic, by reactive species . Enzymatic oxidation leads to an odd series of anti‐inflammatory mediators, similar to aspirin, whereas non‐enzymatic ones generate metabolites capable of acting deleteriously when in excess, modifying the structures and functions of cell membranes .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 On the other hand, as DHA is a polyunsaturated fatty acid and has several carbon double bonds, it becomes a highly susceptible oxidation target, which can be enzymatic by COX and LOX, or non-enzymatic, by reactive species. 28 Enzymatic oxidation leads to an odd series of anti-inflammatory mediators, similar to aspirin, whereas non-enzymatic ones generate metabolites capable of acting deleteriously when in excess, modifying the structures and functions of cell membranes. 29 Considering this background information, it is suggested that the high concentrations of nitrite present in the Griess method used by the present study, associated with peritonitis, may have promoted the non-enzymatic oxidation of DHA and thus interfered with the reducing activity of the associated BCP.…”
Section: Discussionmentioning
confidence: 99%